Recent progress in electrocatalysts and electrodes for portable fuel cells. Issue 32 (3rd August 2021) - Neaţu, Ştefan; Neaţu, Florentina; Chirica, Iuliana M.; Borbáth, Irina; Tálas, Emília; Tompos, András; Somacescu, Simona; Osiceanu, Petre; Folgado, M. Antonia; Chaparro, Antonio M.; Florea, Mihaela
Abstract : This review highlights the recent progress in designing electrocatalysts for producing high performance fuel cells with truly potential applicability to be used in portable devices. Abstract : Fuel cells are devices that transform efficiently the chemical energy of hydrogen or another fuel into clean electricity. The fuel cell technology is attractive for its high-energy efficiency and expanded fuel flexibility and it became very relevant in the last decade. Moreover, the utilization of fuel cells for portable electronic devices has seen remarkable increase in the last few years. Performances of fuel cells, among others, strongly depend on the types of electrocatalysts and membrane, anion exchange or cation exchange, used in the system. Therefore, a status report about the latest advances in electrocatalysts and electrodes for portable fuel cells is the objective of this review paper. Herein, the recent progress in designing electrocatalysts for producing high performance fuel cells with truly potential applicability to be used in portable devices is highlighted.